Gut Microbiota and Lymphocyte Subsets in Canine Leishmaniasis - Meazzi, Sara; Lauzi, Stefania; Martini, Valeria; Ferriani, Riccardo; Peri, Margherita; Zanzani, Sergio Aurelio; Giordano, Alessia (Frontiers in Veterinary Science, 2022)
Gut microbiota seems to interact with immune system. Little is known about the gut microbiota composition in dogs with leishmaniasis, where pathogenesis and clinical signs strongly rely on the host immune response. The aim of this study is to compare the gut microbiota composition and leukocyte subsets of healthy dogs with those of asymptomatic dogs exposed to Leishmania spp. and dogs with clinical leishmaniasis. Thirty-nine dogs were enrolled and grouped into three groups: healthy, exposed asymptomatic and infected symptomatic for Leishmania spp. Flow cytometry on whole blood evaluated the prevalence of CD4, CD5, CD8, CD11b, CD14 and CD21 positive cells. Gut microbiota was investigated using a next generation sequencing (NGS) technique. Firmicutes resulted significantly more abundant in the healthy dogs compared with the other two groups. Conversely, Proteobacteria were more abundant in symptomatic dogs. Significant differences were also found in abundance of less represented phyla and in the comparison at classes, order, family and genus levels. All the lymphocyte classes (CD4, CD5, CD8, CD21) were less represented in the symptomatic group compared to the others. The finding of a lower abundance of Firmicutes in diseased animals agrees with literature, since this phylum is usually more represented in healthy animals. Increased Proteobacteria in sick animals could suggest the presence of a dysbiosis, even in absence of overt gastrointestinal signs. Results about the leukocyte populations indicate a lower Th1 response in symptomatic animals. Studies also investigating the cytokine response could deepen our knowledge on the pathogenesis of canine leishmaniasis.